1964
DOI: 10.1111/j.2044-8295.1964.tb00928.x
|View full text |Cite
|
Sign up to set email alerts
|

Information, Acoustic Confusion and Memory Span

Abstract: Immediately after visual presentation, subjects were required to recall 6-letter sequences. Sequences were drawn from four vocabularies. There were two 3-letter vocabularies, distinguished by the probability of acoustic confusion within them, and two 9-letter vocabularies similarly distinguished. Memory span is shown to be effectively independent of information per item, and to depend substantially on the probability of acoustic confusion within vocabularies.A recent paper by the author (Conrad, 1964) demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
372
2
14

Year Published

1984
1984
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 620 publications
(407 citation statements)
references
References 0 publications
19
372
2
14
Order By: Relevance
“…Conrad and Hull (1964) further substantiated the phonetic nature of short-term memory by showing that recall performance was disrupted by including phonetically similar letters in a memory list. Liberman, Shankweiler, Liberman, Fowler, and Fisher (1977) discovered that the disruption caused by phonetically similar memory items differed for disabled and normal readers (see also Shankweiler, Liberman, Mark, Fowler, & Fisher, 1979).…”
mentioning
confidence: 75%
“…Conrad and Hull (1964) further substantiated the phonetic nature of short-term memory by showing that recall performance was disrupted by including phonetically similar letters in a memory list. Liberman, Shankweiler, Liberman, Fowler, and Fisher (1977) discovered that the disruption caused by phonetically similar memory items differed for disabled and normal readers (see also Shankweiler, Liberman, Mark, Fowler, & Fisher, 1979).…”
mentioning
confidence: 75%
“…In light of our analysis, which revealed that these findings are highly diagnostic for adjudicating between the interference hypothesis and its competitors, filling this gap seems important. One open question, for instance, is whether the benefit of heterogeneous memory sets is more than just an instance of the benefit of dissimilarity within a memory set (Conrad & Hull, 1964;Poirier, Saint-Aubin, Musselwhite, Mohanadas, & Mahammed, 2007). Theoretical Prospects.…”
Section: Empirical Desiderata Whereas Most Of the Findings Inmentioning
confidence: 99%
“…The phonological loop component of the model is in turn composed of a temporary phonological store whose contents decay with time unless refreshed via an articulatory control process. A number of key phenomena have been used to support the phonological loop concept, among them effects of phonological similarity (Conrad, 1964;Conrad & Hull, 1964;Wickelgren, 1965), word length (Baddeley, Thomson, & Buchanan, 1975), irrelevant sound (Colle & Welsh, 1976;Salame & Baddeley, 1982), and concurrent articulation (Baddeley, Lewis, & Vallar, 1984;Levy, 1971;Murray, 1968). On this view, while participants must engage in language production to complete the recall task, an independent storage mechanism is responsible for memory maintenance.…”
Section: Introductionmentioning
confidence: 99%